2022
DOI: 10.3390/su141911908
|View full text |Cite
|
Sign up to set email alerts
|

Fostering Green Finance for Sustainable Development: A Focus on Textile and Leather Small Medium Enterprises in Pakistan

Abstract: The green financing landscape in Pakistan is evolving, which signifies the need for a comprehensive gap analysis that examines the present status and constraints in supporting green finance in the country. Textile and leather industries are key sectors in Pakistan’s economy and rely heavily on small and medium enterprises (SMEs). Excessive resource use and inadequate environmental management methods pose a significant danger to the sectors’ long-term viability and account for an extreme relevance to the embrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 98 publications
0
27
0
Order By: Relevance
“…Green financing, where private banking supports the advancement of conservation measures such as CP through aspects such as low-interest loans, has been successful in other locations outside of Sindh. Financial support from other nations such as Sweden and the Netherlands, as well as the United Nations, has helped to expand CP in Pakistan to date; similar partnerships could help to expand CP in Sindh (Kumar et al, 2022 ). Unfortunately, not all businesses are as open to technology progress as they could be.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Green financing, where private banking supports the advancement of conservation measures such as CP through aspects such as low-interest loans, has been successful in other locations outside of Sindh. Financial support from other nations such as Sweden and the Netherlands, as well as the United Nations, has helped to expand CP in Pakistan to date; similar partnerships could help to expand CP in Sindh (Kumar et al, 2022 ). Unfortunately, not all businesses are as open to technology progress as they could be.…”
Section: Discussionmentioning
confidence: 99%
“…The focus group discussions often allow for both qualitative, quantitative, and observational information. The data from the focus group discussion were interpreted using qualitative analytic approaches such as grounded data investigation (Kumar et al, 2022 ; O.Nyumba et al, 2018 ; Braam et al . , 2020 ), and conversation analyses (Leech & Onwuegbuzie, 2007 , 2008 ).…”
Section: Methodsmentioning
confidence: 99%
“…Hence, sufficient finances are necessary for environmentally friendly practices, whereas ventures with limited finances fail to comply with sustainable activities (Sadiq et al, 2022). Moreover, such enterprises use marginal analysis while indulging in sustainable activities (Kumar et al, 2022), while Scarpellini et al (2018) claim that, due to FR constraints, firms cannot actively participate in and implement eco-innovative activities.…”
Section: Fr and Sustainability Performancementioning
confidence: 99%
“…In recent years, many studies have shown that the green financial market with strong development momentum is crucial to the implementation of renewable energy plans (Soundarrajan et al, 2016;Huang et al, 2021;Zheng et al, 2022). A large number of scholars have concluded that the development of green finance contributes to the achievement of sustainable development goals Kumar et al, 2022;Ibrahim et al, 2022), and generally there is a positive relationship between renewable energy and sustainable development (Lund and Henrik, 2007;Schwerhoff et al, 2017;Solangi et al, 2021). Energy transformation and upgrading help to achieve the sustainable development goals, while sustainable economic development promotes increased investment in renewable energy projects, thus promoting the transformation of energy structure.…”
Section: Introductionmentioning
confidence: 99%